Pengembangan Model Triase Berbasis Intervensi Cest (Caring, Edukasi dan Patient Safety) dalam Meningkatkan Kepuasan Pasien - Panjaitan, Yunita; Haloho, Maria Artaulina; Suryani, Irma; Amalia, Hilda (Universitas Faletehan, 2024)
The suboptimal knowledge and understanding of patients and their families regarding the triage system in emergency department can lead to conflicts due to the feeling of neglected and not receiving definitive action. Therefore, developing a triage model with active interventions of caring, education, and patient safety is required in triage services at emergency department. This study aimed to determine the effects of caring, education, and patient safety (CEST)-based triage model on the level of patient satisfaction at Hermina Hospital, Indonesia. This study used a quantitative approach with a true experimental design using a post-test only group control design. The samples in this study were 30 intervention groups and 30 control groups selected with simple random sampling techniques. The statistical test used was an independent t-test. The results of this study showed that there was a significant difference in patient satisfaction between the control group and the intervention group. The mean of the control group was 26.07 and 29.70 for the intervention group. The p-value of the effects of implementing the CEST triage model between the control and intervention groups was 0.002 (< 0.05). Developing the CEST-based triage model can improve patient satisfaction by providing a sense of caring, education, and implementing patient safety in the hospital.